Dermatological signs in liver transplant recipients. (21st January 2021) - Sarac, Gulbahar; Ozcan, Kubra Nur; Baskiran, Adil; Cenk, Hulya; Sarac, Mehmet; Sener, Serpil; Yilmaz, Sezai
Abstract: Background: In recent years, the number of liver transplantations for advanced‐stage liver diseases has considerably increased and the patients have a wide range of dermatologic manifestations. Aim: This study aims to reveal cutaneous, mucosal, and nail lesions in liver transplant recipients in quite large patient series. Patients/Methods: The study included 520 patients in the Inonu University Liver Transplantation Institute. New and followed‐up patients attended to the study between May and October 2019. The patients were examined by a dermatologist, and their data were recorded. Results: The study included 163 female and 357 male patients with the main age of 44.20 ± 18.18 (range: 1‐83 years), and 465 livers (89.4%) were taken from live donors, while 54 livers (10.4%) were taken from cadavers. A total of 314 (60.4%) patients had dermatophyte infections, 174 (33.4%) patients had pathological nail changes, and 427 (82.1%) patients had oral mucosal lesions. Graft‐versus‐host disease (GVHD) developed in 9 (1.73%) patients after the transplantation, and 5 patients died of GVHD. Four patients had cutaneous malignancies. Conclusions: Tumoral and nontumoral dermatological diseases may be encountered following the transplantation depending on underlying liver disease, immunosuppressive treatment, the graft itself, or any primary cutaneous disease. Liver transplantation recipients require a multidisciplinary clinical approach, and dermatological care must be an integral part of this approach.